Career Development Bagi Praktik Pekerjaan Sosial Dalam Organisasi Pelayanan Sosial - Sukmana, Djulaiha; Nulhaqim, Soni Akhmad; Apsari, Nurliana Cipta (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2024)
The purpose of this writing is to describe the importance of career development (career development) for social work practitioners who work in social organization services. Social workers must obtain human resource (HR) improvement activities to support performance development as professional practitioners, where social workers have an important role in ensuring that the services provided are in accordance with procedures and help improve the functioning of social benefit recipients. The writing method uses a literature review study, namely reviewing 18 (eighteen) scientific articles and books related to the chosen topic. The results of the research carried out show that there are several efforts to develop careers for social workers, namely self-development programs by attending training or workshops, participating in social worker professional certification activities organized by LSPS, improving skills or soft skills, managerial abilities, increasing research and writing. able to encourage social worker productivity. This effort can encourage the career development of social workers and increase the effectiveness of social service organizations in providing services.